Bioaccumulation of pesticides in carabid beetles in a vineyard and olive grove under integrated pest management - Lucija ŠERIĆ JELASKA; Mišel JELIĆ; Barbara ANĐELIĆ DMITROVIĆ; Tomislav KOS (European Journal of Entomology)
Intensive use of pesticides is among the main drivers of biodiversity loss, especially of insects. Here, field concentrations of chemical synthetic pesticides were measured in soil and carabid beetles in a vineyard (VP) and olive grove (OP), in two consecutive years. The aim was to determine if active ingredients in pesticides applied in the field accumulate in carabids and how this correlates with treatment intensity. Carabids and soil samples were collected at a vineyard and olive grove in Zadar County in Croatia, soil in 2018 and 2019 and carabids in 2019. Both were under integrated pest management (IPM), with a total of 34 pesticides applied, between January and August in the two years of this study. Using LC-MS/MS, a broad range of pesticides, mainly fungicides, was detected in the soil and carabids. In soil samples, boscalid (0.047 mg/kg), mandipropamid (0.08 mg/kg), fluopyram (0.09 mg/kg), cyprodinil (0.09 mg/kg) and tebuconazole (0.13 mg/kg) were detected in the highest amounts. In addition, nine substances were detected in carabids, with valiphenalate (0.048 mg/kg), difenoconazole (0.051 mg/kg) and azoxystrobin (0.064 mg/kg) in the highest concentrations. Bioaccumulation factor (BAF) indicated the accumulation of valiphenalate, metalaxyl-M, spiroxamine and difenoconazole in carabids. Data measured directly in the field revealed the accumulation of pesticides in carabids, which indicates they could be good bioindicators in IPM and contribute to a better understanding of the distribution of pesticides in Mediterranean agroecosystems.